Comparative Study Of The Role Of Institutions In Shaping Inventive Activity In Mid-Range Emerging Economies - Ervits, Irina; Żmuda, Małgorzata (Comparative Economic Research. Central and Eastern Europe, 2016)
The objective of this paper is to investigate the effects of institutions on national rates of inventive activity. Invention, part of the innovation process, is acknowledged as one of the driving forces behind economic growth, and patent statistics are frequently used as a measurable indicator of inventive output. Thus this paper explores the relationship between national patent statistics and measures of institutional quality. As a result of our research, the effect of the “threshold of inventive activity” was observed. This effect demonstrates that when countries reach a certain level of institutional development and attain a general institutional climate conducive to inventive activity, the number of patent applications begins to sharply increase. The paper contributes to the body of evidence that confirms that a combination of fundamental institutions like the rule of law or freedom of expression, which are not necessarily aimed at boosting innovation, create an overall environment conducive to patenting. We demonstrate that “mid-range emerging economies”, including those in Central and Eastern Europe (CEE), where the quality of institutions is lagging behind more developed counterparts and/or their influence is weak or sporadic, have not yet reached the threshold of inventive activity yet. However, those CEE countries that have acceded to the European Union first have made visible progress with respect to institutional quality and invention.